Local Community Perception Analysis in Border Dispute Settlement: A Study in Central Maluku, Indonesia - Suat, Hatty; Borut, Muhammad; Talakua, Jeane (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study analyzes the local community's perception in settling the border dispute between Central Maluku Regency and West Seram Regency in Indonesia, specifically in the Elpaputih district which includes Samasuru, Sahulau, and Paulohi villages. The research focuses on two main issues: the constitutional implications and the implementation of regional autonomy in defining the administrative and governance boundaries in the Elpaputih district. The theoretical framework employed in this research includes analysis, perception, conflict, and border theory. The qualitative analysis process includes data reduction, data summary, and drawing conclusions. The study finds that both parties need to prepare themselves for reconciliation by acknowledging the conflict's reality and the interests of the other party. They also need to organize their interests clearly and agree on the rules of the game that will guide their relationship and interaction. This research provides valuable insights into the local community's perception in settling border disputes, which can be beneficial for policymakers and other stakeholders in resolving similar conflicts in other regions.